PROKRASTINASI AKADEMIK MAHASISWA DITINJAU DARI SELF REGULATED LEARNING DAN DUKUNGAN SOSIAL - Elfrida Astin Hanadia; Nur Ainy Sadijah; Haryanti Mustika (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Academic procrastination is a major concern among university students because it is associated with delayed task completion and poorer academic performance. Although self-regulated learning and social support have been widely investigated, evidence regarding their combined contribution and the specific roles of different sources of social support among students at Buana Perjuangan University Karawang remains limited. This study aimed to examine the extent to which self-regulated learning and social support predict academic procrastination among 335 students at Buana Perjuangan University Karawang selected through proportionate stratified sampling. This quantitative study employed a correlational design using the Academic Procrastination Scale (APS), the Academic Self-Regulated Learning Scale (A-SRL-S), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using multiple linear regression with SPSS version 25. The results showed that self-regulated learning and social support jointly predicted academic procrastination. Individually, both variables were negatively associated with academic procrastination, with self-regulated learning emerging as the stronger predictor. Among the three sources of social support, only support from significant others significantly predicted academic procrastination, whereas support from family and friends did not make significant contributions. Most students demonstrated high levels of academic procrastination, low self-regulated learning, and high perceived social support. These findings indicate that better self-regulated learning and stronger support from significant others are associated with lower levels of academic procrastination among university students. ABSTRAK Prokrastinasi akademik merupakan permasalahan penting pada mahasiswa karena berkaitan dengan keterlambatan penyelesaian tugas dan rendahnya pencapaian akademik. Meskipun self-regulated learning dan dukungan sosial telah banyak dikaji, bukti mengenai kontribusi simultan kedua variabel serta peran spesifik setiap sumber dukungan sosial pada mahasiswa Universitas Buana Perjuangan Karawang masih terbatas. Penelitian ini bertujuan menganalisis kemampuan self-regulated learning dan dukungan sosial dalam memprediksi prokrastinasi akademik pada 335 mahasiswa Universitas Buana Perjuangan Karawang yang dipilih melalui proportionate stratified sampling. Penelitian kuantitatif dengan desain korelasional ini menggunakan Academic Procrastination Scale (APS), Academic Self-Regulated Learning Scale (A-SRL-S), dan Multidimensional Scale of Perceived Social Support (MSPSS). Data dianalisis menggunakan regresi linear berganda dengan bantuan SPSS 25. Hasil penelitian menunjukkan bahwa self-regulated learning dan dukungan sosial secara simultan memprediksi prokrastinasi akademik. Secara parsial, kedua variabel berasosiasi negatif dengan prokrastinasi akademik, dengan self-regulated learning sebagai prediktor yang lebih kuat. Dari ketiga sumber dukungan sosial, hanya dukungan dari significant others yang menjadi prediktor signifikan, sedangkan dukungan keluarga dan teman tidak menunjukkan kontribusi yang signifikan. Mayoritas mahasiswa memiliki prokrastinasi akademik tinggi, self-regulated learning rendah, dan dukungan sosial tinggi. Temuan ini menunjukkan bahwa self-regulated learning yang lebih baik dan dukungan yang lebih tinggi dari significant others berasosiasi dengan rendahnya prokrastinasi akademik mahasiswa.